Endothelial Function and Postprandial Glucose Control in Response to Test-Meals Containing Herbs and Spices in Adults With Overweight/Obesity - Huang, Yudai; Tsai, Meng-Fu; Thorat, Rajrajeshwari Sunil; Xiao, Di; Zhang, Xuhuiqun; Sandhu, Amandeep K.; Edirisinghe, Indika; Burton-Freeman, Britt M. (Frontiers in Nutrition, 2022)
Objectives Herbs and Spices (H/S) contain bioactive compounds with purported health benefits. This study investigated the effect of H/S intake on indicators of vascular and metabolic health over 24 h using a test-meal challenge paradigm in adults with overweight or obesity. Methods In a randomized, single-blinded, 4-arm, 24 h, multi-sampling, crossover clinical trial, adults (n = 25) aged 36.6 ± 3.1 years with BMI 28.5 ± 0.6 kg/m2 (mean ± SEM) consumed a high-fat, high-carbohydrate challenge meal (~810 kcal) with salt/pepper only (control) or control with one of three different H/S combinations: Italian herb (rosemary, basil, thyme, oregano, and parsley), cinnamon, or pumpkin pie spice mix (cinnamon, ginger, nutmeg, and allspice) on four separate visits at least 3 days apart. Meals provided 35% of subjects' energy to maintain weight and ~1 g H/S per 135 kcal of the meal. Flow-mediated dilation (FMD) and blood samples were collected at 0, 1, 2, 4, 5.5, 7, and 24 h for endpoint analysis (additional blood draw at 0.5 h for insulin/glucose). Mixed-model analysis of repeated measures via PROC MIXED PC-SAS 9.4 was performed on the primary outcome (FMD) and secondary outcome variables. This study was registered at ClinicalTrials.gov (NCT03926442). Results Italian herb and pumpkin spice meals significantly increased %FMD at 24 h compared to the control meal (P = 0.048 and P = 0.027, respectively). The cinnamon meal reduced postprandial glycemia (Δ) compared to control (P = 0.01), and pumpkin pie spice mix and cinnamon meals reduced postprandial insulin at 0.5 h compared to the control meal (P = 0.01 and P = 0.04, respectively). IL-6 and triglycerides increased in response to all meals (Time, P < 0.0001) but were not significantly different between meals. Conclusions The test-meal challenge study design coupled with multiple sampling over 24 h provides insights into time-course bioactivity of H/S on vascular function and metabolic indices in overweight/obese adults. Clinical Trial Registration ClinicalTrials.gov, identifier: NCT03926442.